Milk, meaning, and morality: Following the trajectory of donated breast milk from donor to baby (Medicine Anthropology Theory, 2016)
Donated human milk’s status comes into question as it leaves the mother-child relationship and is reconfigured through practices and discursive structures that seek to stabilise it as a specific kind of object. Based on research conducted in Cape Town, South Africa, we examine the crucial role of technologies in aiding the milk’s transformation as milk moves from donors’ homes into the clinical setting where it is received by preterm, low-birth weight newborns. We show that the milk shifts back and forth between being a bodily fluid, food, and medicine in the course of this trajectory. Different techniques foreground milk’s diverse properties as a set of moral decisions converges around saving, securing, and sustaining life, and materialising relationships.